What to expect in the interrogation room? - Klaudia Lohner; Zsóka Mária Bellavics (Belügyi Szemle)
Aim: The aim of the present paper is to provide specific techniques in the support of the interrogation of sex offenders beyond the basic level applying international and domestic empirical findings.